Variability and Inconsistency of Titles for Part-time Faculty Appointments at US Medical Schools - DeBroff, Brian M. (Archives of Clinical and Biomedical Research, 2024)
US medical faculty are increasing the number of part-time, voluntary, and clinical faculty members as academic facilities expand and acquire an increasing number of community clinical practices. Academic institutions have used variable, inconsistent, and often overlapping titles for their part-time faculty. This paper identifies, categorizes, and analyzes the variability in titles used to describe the part-time medical school faculty and distinguish these faculty from full-time, ladder or tenure track faculty at US medical schools. Suggestions for simplifying and unifying the nomenclature are proposed as a method to create uniformity and consistency and avoid confusion among member of academia, the public, and the patient population.